Odpowiedzi

2010-02-10T22:34:55+01:00
X - pierwsza liczba
3 x - druga liczba
3 x - 1 - trzecia liczba

x + 3 x + 3 x - 1 = x + 23
6 x = 24
x = 4

4 - pierwsza liczba
3 * 4=12 - druga liczba
3 * 4-1=11 - trzecia liczba

Odp: Ania dodała liczby: 4, 12 i 11.

1 5 1
2010-02-10T22:36:34+01:00
X-1 liczba
y- 2 liczba
z-3 liczba

x+3x+3x-1=x-23
7x-1=x-23
6x=24 /:6
x=4


Sprawdzenie:
4+12+11=27
27-4=23
2010-02-10T22:37:27+01:00
1- x = 4
2- 3x = 12
3- 3x - 1 = 11

x+3x+3x-1=x+23
7x=x+23+1
7x=x+24
7x-x=24
6x=24
x=4